2019
DOI: 10.1101/859637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methylphenidate boosts choices of mental labor over leisure depending on baseline striatal dopamine

Abstract: The cognitive enhancing effects of methylphenidate are well established, but the mechanisms remain unclear. We recently demonstrated that methylphenidate boosts cognitive motivation by enhancing the weight on the benefits of a cognitive task in a manner that depended on striatal dopamine. Here we considered the complementary hypothesis that methylphenidate might also act by changing the weight on the opportunity cost of a cognitive task. To this end, fifty healthy participants (25 women) completed a novel cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
1
3
1
Order By: Relevance
“…For example, the current design does not disconfirm previously demonstrated and replicated links between motivation, cognitive control and polymorphisms in the dopamine transporter gene 3,14,18 , dopamine release 37 or dopamine-related disease status 13,38,39 . Similarly, the current failure to replicate does not undermine other studies demonstrating a link between dopamine synthesis capacity and cognitive motivation indexed with other tasks, such as delay discounting 40 , cognitive effort discounting 23,24 or reward-based reversal learning 41 . Nevertheless, the presently observed lack of effect reduces our confidence in the link between dopamine synthesis capacity and the effect of a promised reward on Stroop interference and stresses the need for further studies.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…For example, the current design does not disconfirm previously demonstrated and replicated links between motivation, cognitive control and polymorphisms in the dopamine transporter gene 3,14,18 , dopamine release 37 or dopamine-related disease status 13,38,39 . Similarly, the current failure to replicate does not undermine other studies demonstrating a link between dopamine synthesis capacity and cognitive motivation indexed with other tasks, such as delay discounting 40 , cognitive effort discounting 23,24 or reward-based reversal learning 41 . Nevertheless, the presently observed lack of effect reduces our confidence in the link between dopamine synthesis capacity and the effect of a promised reward on Stroop interference and stresses the need for further studies.…”
Section: Discussioncontrasting
confidence: 39%
“…We supplemented the analyses with voxelwise correlations of the behavioral measures with dopamine synthesis capacity. Critically, striatal dopamine synthesis capacity in this new sample had already been indexed in the context of a previous study not reported here (www.trial regis ter.nl/trial /5959; data of which were previously included in Westbrook et al 23 and Hofmans et al 24 ), using [ 18 F]DOPA PET. This is unlike the original study, in which [ 18 F]FMT PET was used to index striatal dopamine synthesis capacity.…”
mentioning
confidence: 99%
“…This interpretation is consistent with results of correlations between ERN amplitudes and learning from punishments in healthy subjects (Frank et al, 2005). This leads to speculation that people with lower ERNs and lower tendencies to learn from punishments may be characterized by higher levels of striatal dopamine, consistent with findings suggesting positive correlation between impulsivity and striatal dopamine measures (Buckholtz et al, 2010;Hofmans et al, 2019). Buckholtz and colleagues suggested that high levels of striatal dopamine in impulsive subjects may result from lower levels of D2/D3 autoreceptors in the substantia nigra and ventral tegmental area leading to stronger dopamine cell activity and enhanced release of dopamine which could in turn increase impulsivity and promote "Go" behaviors (Buckholtz et al, 2010).…”
Section: Possible Mechanismssupporting
confidence: 87%
“…The data reported here were acquired in the context of a larger pharmacological PET/fMRI study, components of which have been and will be reported separately (Hofmans et al, 2020(Hofmans et al, , 2022Määttä et al, 2021;van den Bosch, Hezemans, et al, 2022;van den Bosch, Lambregts, et al, 2022;Westbrook et al, 2020; an overview of the complete study at https://osf.io/d3h8e). For this study, participants paid five visits.…”
Section: General Proceduresmentioning
confidence: 99%